The Impact of Foreign Direct Investment on Productivity of Domestic Firms: The Case of Sudanese Banking Industry (International Journal of Scientific Research and Management (IJSRM), 2021)
The research expands existing international business literature by exploring the impact of Foreign Direct Investment (FDI) on domestic banks. It investigates how FDI affects the productivity of domestic banks in Sudan. Many countries strive to attract foreign direct investment (FDI) hoping that knowledge brought by FDI will spillover to domestic industries and increase their productivity. In contrast with earlier literature that tried to find positive interindustry spillovers from multinationals, this study focuses on effects operating in banking industry. The analysis, based on firm-level data from Sudan , the results show evidence consistent with positive productivity spillovers from FDI taking place through contacts between foreign affiliates and their local counterparts . The data indicate that productivity spillovers are associated with foreign owned banks.